Meta-analysis of the performance of ultrathin vs. standard colonoscopes - Sofi, Aijaz Ahmed; Nawras, Ali; Khan, Muhammad Ali; Howden, Colin W.; Lee, Wade M. (Endoscopy, 2017)
Background and study aims Colonoscopy should reliably intubate the cecum with minimal patient discomfort and without complications. Use of thinner endoscopes to overcome pain during the procedure has shown promise. However, the use of thinner scopes could lead to excess looping and difficulty with therapeutic procedures. The aim of this meta-analysis was to analyze the performance of ultrathin colonoscopes (UTC) and standard colonoscopes for routine colonoscopy.Patients and methods We searched several electronic databases for all randomized controlled trials and nonrandomized (prospective) studies that compared the efficacies of UTC (diameter ≤ 9.8 mm) and standard colonoscopes. We used fixed effect or random effects models to compare cecal intubation rate, cecal intubation time, pain score, and polyp and adenoma detection rates using standard mean differences (SMD) or odds ratios (OR) with 95 % confidence intervals (CI).Results Seven studies (2191 patients) met the inclusion criteria. There was no significant heterogeneity among studies except for pain scores. The cecal intubation rate was higher with UTC (OR 2.30; 95 %CI 1.31 to 4.03). There was no difference in the cecal intubation time between UTC and standard colonoscopes. Pain scores were significantly lower with UTC than with standard colonoscopes (SMD – 0.59, 95 %CI – 0.93 to – 0.25). Polyp and adenoma detection rates were similar for both types of colonoscope.Conclusion Use of UTC appears to improve the cecal intubation rate and reduce abdominal pain but does not affect polyp detection. Future trials are needed to evaluate the therapeutic performance of UTC vs. standard colonoscopes.